The cultural and religious conflict between Korean wave and Islamic values - Wan Kamal Mujani,; Rou, Seung Yoan; Keum, Hyun Kim (Penerbit Universiti Kebangsaan Malaysia, 2022)
Korean popular culture, such as movies, TV dramas, and pop music, is overwhelmingly powerful and TV dramas are especially remarkably popular in terms of obsession of fans and audiences. They also bring considerable profit to South Korea. The Korean Wave (Hallyu) brings a different level of Korean fever in certain East Asian countries, including Malaysia. By introducing new story materials, and using hi-tech skills in shooting, K-Dramas continue to gain popularity especially in the genre of historical drama that provides newly interpreted viewpoints about many historical stories. These continuous efforts in the fields of K-Pop, K-Food and K-Fashion expand areas and brighten the future of Korean Wave. The universality of cultures and values, which is the strength of the Korean Wave, is a unifying force to draw the minds of the people around the world and to make them enthusiastic about the Korean Wave. At the same time, there is also a possibility of conflict between Korean Wave and Islamic values, including in Malaysia. Muslim Korean Wave lovers are suffering from cultural and religious conflict between Korean and Islamic values and even experiencing anomie and dilemma such that they are not free from the criticisms of their own communities.